1992
DOI: 10.1128/jb.174.7.2407-2411.1992
|View full text |Cite
|
Sign up to set email alerts
|

Common antigen lipopolysaccharide from Pseudomonas aeruginosa AK1401 as a receptor for bacteriophage A7

Abstract: A-band, a D-rhamnose-containing common lipopolysaccharide antigen isolated from Pseudomonas aeruginosa AK1401, was found to be a receptor for bacteriophage A7. The phage-borne rhamnanase was capable of hydrolyzing the A-band to expose core-lipid A containing only two or three rhamnose repeats. Interaction of the hydrolyzed A-band with core-or lipid A-specific monoclonal antibodies revealed that common epitopes exist in the inner core and lipid A regions, while the outer core of A-band appears to be different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…CPA was found to be a receptor for bacteriophage A7 (27) and for lectin-like bacteriocins (28). Lectin-like bacteriocins, such as pyocin L1 and putidacin L1, display a genus-specific killing activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPA was found to be a receptor for bacteriophage A7 (27) and for lectin-like bacteriocins (28). Lectin-like bacteriocins, such as pyocin L1 and putidacin L1, display a genus-specific killing activity.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the latter operon to CPA biosynthesis has been established based on evidence collected from mutagenesis and overexpression experiments (25). CPA was found to play important biological roles as a receptor for bacteriophage A7 (27) and lectin-like bacteriocins (28) and as a surface antigen for P. aeruginosa that is important for adherence to human bronchial epithelial cells (29). In a recent study, Murphy et al (30) showed that CPA is required for strain PAO1 to develop mature and robust biofilms.…”
mentioning
confidence: 99%
“…Acid hydrolysis cleaves the ketosidic linkage between the Kdo residue and the lipid A molecule. This treatment was used effectively in a previous study (46), and it essentially dissociates the core oligosaccharide and O-polysaccharide moieties, leaving only the unsubstituted lipid A molecule. In nonhydrolyzed immunoblots, MAb 177 reacted with only a single fast-migrating LPS band (Fig.…”
Section: Matermils and Methodsmentioning
confidence: 99%
“…Bastin et al (2) suggested that Wzz acts as a molecular timer, allowing polymerization by Wzy to continue either for a set amount of time or until a particular length of O antigen has formed, at which point the polymer is transferred onto lipid A core. An alternate hypothesis, proposed by Morona and colleagues (37), is that Wzz acts as a molecular chaperone, influencing the stoichiometry of Wzy and the O-antigen ligase, WaaL (RfaL [34]), such that the balance between polymerization and ligation events is altered.Pseudomonas aeruginosa is a gram-negative, opportunistic pathogen which produces a number of virulence factors, including exopolysaccharides such as alginate and two distinct forms of LPS (9,36,40). A-band LPS, the common antigen, is expressed by most serotypes and contains a homopolymer of ␣-D-rhamnose (30).…”
mentioning
confidence: 99%
“…Pseudomonas aeruginosa is a gram-negative, opportunistic pathogen which produces a number of virulence factors, including exopolysaccharides such as alginate and two distinct forms of LPS (9,36,40). A-band LPS, the common antigen, is expressed by most serotypes and contains a homopolymer of ␣-D-rhamnose (30).…”
mentioning
confidence: 99%